Transforming large XML documents an alternative to XSLT. - Roy, Indroniel Deb
With the evolution of XML, the XSL standard also became very popular for transforming XML data to XML, text, PDF, etc. However, there are some limitations to the XSLT transformation. Today's XSLT processors rely on holding input data in memory as a DOM tree while the transformation is taking place. The tree structure in memory can be as much as ten times the original data size, so in practice, the limit on data size for an XSLT conversion is just a few megabytes. As a result it can only handle XML documents with moderate size-to be processed as the full input, DOM needs to be in the memory for any XSL transformation.